THE EXPERIENCES OF YOUTHS WHO LEFT CHILD AND YOUTH CARE CENTRES OF THE EKURHULENI METRO MUNICIPALITY DURING THE COVID-19 PANDEMIC - Fadzaishe Bridget Zingwe; Maditobane Robert Lekganyane (Social Work/Maatskaplike Werk, 2024)
Leaving a familiar environment can be daunting. Although previous studies investigated the experiences of youths who left care centres, few considered those who left during the Covid-19 pandemic. For this exploratory qualitative research study, we purposively recruited 12 African youths aged between 18 and 23, with least two years’ experience of life in the care centres of Ekurhuleni Metro Municipality to investigate their experiences when they left such centres during the Covid-19 pandemic. The data were collected through individual semistructured interviews, analysed according to Akinyonde and Khan’s thematic analysis method, and verified using Guba and Lincoln’s strategies. The findings revealed experiences that were clustered into three themes: preparing to leave, reflecting on life at the centre, and transiting from care during Covid-19. The recommendations proposed include the need to facilitate exit strategies for these youths, clear follow-up plans to support them, and collaboration of practitioners in the field of child and youth care.